Lifestyle diseases and effects of the treatment expenditure on family finances (Journal of Applied and Natural Science, 2018)
Health is among the basic capabilities that give value to human life. Good health is a prerequisite to successful human endeavor and core to financial growth and activity. The lifestyle diseases are associated with the way a person or group of people lives. Irregular food habits, physical inactivity, sedentary lifestyles, tobacco, alcohol, high intake of salts and low intake of fruits and vegetables, causes lifestyle diseases. This study was focused on framing the effects of the lifestyle disease treatment’s expenditure on the family finances. A survey of 120 respondents in Hyderabad and Secunderabad cities was conducted. Some of the effects mentioned by the respondents were “Inability to meet daily needs, incapable of meeting specific needs (newspaper, internet connection, etc.), fiddle with the amount spent for entertainment, kill the amount spent for family shopping, trim down the amount spent on educational activities of children, negotiate with children’s needs, helpless to save for the future planning of the family, inept to pay insurance policies, obtain loan in order to meet the treatment costs, sell assets to meet the treatment expenditure. ”Statistical analysis was carried out by using chi- square tests. The study found that 49% of the families were unable to meet daily needs,54% of them negotiated with children’s needs, 65% of them were helpless to save for the family’s future. The result showed significant association between family finances and the cost of lifestyle disease treatment expenditures based on income levels.